Profil Enzim Hati (SGOT/SGPT) Sebagai Indikator Kesehatan Hepatik Pada Populasi Geriatri di Panti Werdha Hana - Hawari, Irawaty; Santoso, Alexander Halim; Gunaidi, Farell Christian; Dewanto, Paulus Gegana Thery; Rafif, Akhtar Nawfal (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Liver dysfunction is a common health issue among the elderly and can significantly impact quality of life, particularly due to its progressive nature and frequently asymptomatic presentation in the early stages. Many older adults are unaware of liver problems, as mild symptoms such as fatigue, abdominal discomfort, or reduced appetite are often perceived as normal signs of aging. The Community Service Program (PKM) conducted at Panti Werdha Hana aimed to raise awareness among the elderly regarding the importance of early detection of liver dysfunction through SGOT and SGPT enzyme screening. This activity employed the Plan-Do-Check-Act (PDCA) approach, including laboratory examinations and interactive counseling on risk factors, healthy lifestyle practices, and the significance of regular health monitoring. Among the 76 participants, 10 individuals (13.16%) were found to have elevated SGOT levels, and 8 individuals (7.89%) had SGPT levels above the normal range. These findings underscore the importance of early detection in preventing the progression of chronic liver diseases, enhancing the quality of life of the elderly, and supporting more effective and sustainable healthcare interventions.